Implementasi Sistem Informasi Administrasi Perkantoran Sebagai Upaya Modernisasi Manajemen - Annisa, Nurin; Kurniadi, Ryan (Jurnal Syntax Fusion, 2024)
The development of information technology has brought significant changes to modern office administration management. This study aims to analyze the implementation of Office Administration Information Systems as an effort to modernize management in improving efficiency and service quality. The research method used is qualitative with a case study approach in an office organization. Data collection was conducted through in-depth interviews with employees directly involved in using the system, observations of administrative processes, and documentation related to system implementation. The research results show that the implementation of Office Administration Information Systems has proven to significantly improve time efficiency and data accuracy. This system facilitates employees in performing administrative tasks such as archive management, processing incoming and outgoing correspondence, and report preparation. Manual processes that previously took a long time can be replaced with faster and more structured automated processes. However, this implementation also faces several challenges, particularly regarding employee training needs and the adaptation process to technological changes. This study concludes that Office Administration Information Systems represent a strategic step in office management modernization that provides significant benefits in the form of improved operational efficiency and reduced human error in administrative processes.